O clima urbano em Alfredo Marcondes/SP: uma análise dos indicadores geoambientais - Rampazzo, Camila Riboli [UNESP] (Universidade Estadual Paulista (Unesp), 2012)
There are obvious changes that occur within the cities, experienced in synthesis for the degradation of the environment and especially the worsening quality of life. Even small cities, began to exhibit characteristics typical of an atmospheric climate. Thus, it becomes natural to analyze the characteristics of these spaces, unlike the medium and large cities, provide a detailed analysis of the peculiarities of intra-urban space in order to highlight what factors enhance or soften the formations of a typical urban climate distinct patterns of land use. The aim of this research from a geoenvironmental mapping of attributes (uses and land cover, vegetation and tree characteristics of buildings) while representing the dynamic City entertainment. Thus, we seek to inter-relate these indicators to analysis climate urban-rural and intra-urban applied to the city of Alfredo Marcondes / SP, a small town in order to identify a potential compromise climate conditions point to generate a specific climate. From this detailed analysis, we intend to give suggestions with the government to improve the comfort of that environment. For the data collection was organized a specific methodology for its collection, organization and representation and for the record of climatic data (temperature, wind speed and direction and cloud cover) were used mini-shelters weather with temperature sensors in fixed locations, and a temperature sensor attached on the side of a vehicle, 1.5 meters in height from the floor for 42 points perpassando selected in different intra-urban spaces... (Complete abstract click electronic access below)

São evidentes as transformações que ocorrem no espaço das cidades, sentidas em síntese pela degradação da qualidade do ambiente e principalmente o agravamento da qualidade de vida da população. Até mesmo as cidades de pequeno porte, passaram a apresentar características atmosféricas típicas de um clima local. Assim, se torna singular analisar as particularidades destes espaços que, diferente das médias e grandes cidades, possibilitam uma análise detalhada das particularidades do espaço intra-urbano no intuito de evidenciar quais os fatores que potencializam ou que amenizam as formações de um clima tipicamente urbano em distintos padrões de uso do solo. Pretende-se com esta pesquisa partir de uma representação dos atributos geoambientais (usos e ocupação do solo, vegetação arbórea e características das edificações) enquanto representativos das dinâmicas citadinas. Com isso, busca-se inter-relacionar estes indicadores com a análise climática urbano-rural e intra-urbana aplicada à cidade de Alfredo Marcondes/SP, uma cidade de pequeno porte, a fim de identificar um possível comprometimento das condições climáticas a ponto de gerar um clima específico. A partir desta análise detalhada, pretende-se dar sugestões junto ao poder público para melhorar as condições de conforto de tal ambiente... (Resumo completo, clicar acesso eletrônico abaixo)
Keywords: Geografia; Cidades e vilas; Espaço em geografia; Álvares Machado (SP) - Clima